Determinants of Micro-Entrepreneurial Income in Emerging Urban Tourism Spaces: An Islamic Economic Perspective from Metro City, Lampung - Damara Putra, Riyan; Hotman (Journal of Islamic Finance and Economic Studies, 2025)
Background: Urban public spaces increasingly serve dual roles as recreational sites and economic hubs, offering opportunities for micro-entrepreneurs. Samber Park, located in Metro City, Indonesia, is one such area where relocated street vendors have established businesses, contributing to local economic growth. Aims: This study aims to analyze the key factors influencing the income of micro-entrepreneurs operating at Samber Park, using an Islamic economic perspective to explore how ethical and religious values shape entrepreneurial practices. Methods: The research applies a qualitative descriptive approach. Data were collected through semi-structured interviews with five entrepreneurs and a representative from the local Youth, Sports, and Tourism Office. Data analysis involved data reduction, presentation, and inductive conclusion drawing to ensure rich, contextual findings. Results: The findings reveal that initial capital investment, business location, operating hours, and business tenure significantly affect income levels. Entrepreneurs with strategic locations, extended working hours, and consistent business operation periods tend to earn higher daily incomes, ranging from IDR 100,000 to IDR 300,000. Furthermore, entrepreneurs demonstrate compliance with Islamic economic principles by emphasizing honesty, patience, lawful earnings, and contributing positively to the community. Conclusion: Income generation among micro-entrepreneurs at Samber Park is influenced by both business management factors and adherence to Islamic ethical guidelines. These findings highlight the importance of integrating religious values into entrepreneurial development strategies to promote sustainable and inclusive economic growth.